2015
DOI: 10.18186/jte.53738
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Geometric and Load Perturbation to Buckling in Multilayered Torispherical Pressure Vessel Heads

Abstract: The object of this paper is to investigate the effects of geometry and load perturbation to buckling in multilayered pressure vessel heads. The pressure vessel head in concern is thin walled torispherical geometry. Geometric and load perturbation can alter both the critical load for buckling and the buckled shape. Two and three layered torsispherical heads are considered. Two layered models include steel-aluminum and titanium-aluminum configurations and three layered models include copper-steel-copper configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In the study, two-layer (steel -aluminum and titanium -aluminum configurations) and three-layer (copper -steel -copper) torispheric heads are considered. As a result of this study; it was concluded that in steel-aluminum configurations for two-layer structures, geometric perturbation is more critical than load perturbation, and geometric and load perturbation cause the structure to buckling at a lower pressure value [19].…”
Section: Introductionmentioning
confidence: 86%
“…In the study, two-layer (steel -aluminum and titanium -aluminum configurations) and three-layer (copper -steel -copper) torispheric heads are considered. As a result of this study; it was concluded that in steel-aluminum configurations for two-layer structures, geometric perturbation is more critical than load perturbation, and geometric and load perturbation cause the structure to buckling at a lower pressure value [19].…”
Section: Introductionmentioning
confidence: 86%